Implementation of Game Design Document (GDD) in the Development of the 2D Android-Based Game Komodo Isle - Retno, Sujacka (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2025)
Game development techniques have evolved in this technological era in line with the rapid advancement of technology. Considering the significant influence of technology today, where young children are already familiar with and proficient in operating technological devices such as mobile phones, this phenomenon can be leveraged for more positive purposes. One such approach is introducing Indonesian culture to children through game-based applications. This study presents an Android-based game application that features one of Indonesia's protected animals as the main character—the Komodo, which originates from the province of East Nusa Tenggara. The game development technique used in this study follows the Game Design Document (GDD) framework, which includes Core Loop, Core Mechanics, and Asset Design. This research aims to serve as a positive initiative to increase children's interest in Indonesian culture, ensuring that Indonesia's noble cultural heritage can be effectively conveyed to the younger generation in the digital era. Additionally, this study can serve as a reference for future research, particularly in game development techniques.